Policies Towards Reducing In Work Poverty: An Evaluation on Turkey - Görkey, Selda (My University, 2019)
The interaction between work and poverty has been examined for many years by emphasizing the necessity of being employed as a way out of poverty. However, the experiences of the last decades clearly show that it is not sufficient only to find a job to avoid poverty. Today, many people are classified as poor, even though they are currently working. This issue, called as in work poverty, combines poverty and labor market together, and it is analyzed within the context of inequality in many countries. However, the problem is crucial particularly in developing and emerging countries. As an EU candidate emerging country, Turkey had 13.5% of in work poverty rate in 2016; whereas it was 9.6% in EU-28, according to Eurostat. These rates clarify that in work poverty is a crucial issue in Turkey. Despite its significance, the literature is not rich in studies that focus on the issue for Turkey. İnan attempt to contribute to the literature, this study explains the concept of in work poverty and how it results in inequality in an economy. After that, it points out necessary policies that can be used to reduce in work poverty. The ultimate aim of this study is to examine relevant policies in Turkey, and make an evaluation on the success of these policies. The findings of the research indicate that, the policies in Turkey do not focus solely on in work poverty, instead the problem is generally addressed within the context of poverty, labor market or social policy issues. As a natural consequence of this situation, the issue remains as a crucial problem for both the economy and the society. Thus, this study's another contribution lies in its effort to point out the importance of recognizing the issue specifically for working poor, and then to offer various policies to alleviate in work poverty in Turkey.
Keywords: Working Poverty; Working Poor; Poverty Alleviation; Çalışma Yoksulluğu; Yoksul Çalışan; Yoksulluğun Azaltılması